2019
DOI: 10.1002/ece3.5392
|View full text |Cite
|
Sign up to set email alerts
|

Influences of two coexisting endosymbionts, CI‐inducing Wolbachia and male‐killing Spiroplasma, on the performance of their host Laodelphax striatellus (Hemiptera: Delphacidae)

Abstract: The small brown planthopper Laodelphax striatellus (Hemiptera: Delphacidae) is reported to have the endosymbiont Wolbachia , which shows a strong cytoplasmic incompatibility (CI) between infected males and uninfected females. In the 2000s, female‐biased L. striatellus populations were found in Taiwan, and this sex ratio distortion was the result of male‐killing induced by the infection of another endosymbiont, Spiroplasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…However, this reduction effect does not always occur, such as in Anopheles coluzzii ( 37 ). In pests infected with two endosymbionts, one of them usually has a dominant effect on the bacterial microbiota ( 38 40 ). For example, in drosophilid flies, which were infected with both Wolbachia and Spiroplasma , Wolbachia had a much greater impact on microbes ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this reduction effect does not always occur, such as in Anopheles coluzzii ( 37 ). In pests infected with two endosymbionts, one of them usually has a dominant effect on the bacterial microbiota ( 38 40 ). For example, in drosophilid flies, which were infected with both Wolbachia and Spiroplasma , Wolbachia had a much greater impact on microbes ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…We searched for relevant literature using keyword searches in Web of Science finding articles published until the end of 2019 (details for each group below). Literature and data pertaining to other herbivorous sucking insects was searched for, but with few articles relevant to our meta‐analyses; data for three Auchenorrhyncha species hosting symbionts was extracted but this taxa does not belong to any of the three identified groups and was insufficient to analyse independently (Li et al, 2019; Shentu et al, 2019; Yoshida et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…For this result, we propose such a conjecture, Spiroplasma and Wolbachia in this study may have a competitive relationship. Cause male-killing Spiroplasma infection obstructs the spread of CI-inducing Wolbachia infection ( Yoshida et al, 2019 ). The ripeness of the feeding material is positively related to the relative abundance of Spiroplasma in E. brandti and Wolbachia in E. scrobiculatus .…”
Section: Discussionmentioning
confidence: 99%
“…The ripeness of the feeding material is positively related to the relative abundance of Spiroplasma in E. brandti and Wolbachia in E. scrobiculatus . A trunk diet might result in reproductive isolation between E. brandti and E. scrobiculatus , as the relative abundance of Wolbachia and gene flow toward the MK-infected island is increased when the relative abundance of Spiroplasma is high ( Engelstadter et al, 2008 ; Yoshida et al, 2019 ). However, some previous studies have shown that the abundance of Wolbachia in the gut is higher in laboratory environments, but the reason for this pattern remains unclear ( Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%